2014
DOI: 10.1177/1352458514561907
|View full text |Cite
|
Sign up to set email alerts
|

Parity is associated with a longer time to reach irreversible disability milestones in women with multiple sclerosis

Abstract: Our findings suggest that pregnancy after MS onset is associated with a slower long-term disability progression. Whether this represents a biological/immunological effect, or reflects a higher propensity toward childbearing in women with milder disease, it remains uncertain deserving further investigations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 20 publications
1
39
0
1
Order By: Relevance
“…Most of the studies have not shown any negative effect of a pregnancy on long-term disease course/progression or disability [32]; some even reported favorable effects [12,29,31]. We showed that MS patients who had only 1 pregnancy had a higher conversion rate from RRMS to SPMS than MS patients with 2 or more pregnancies (p = 0.001).…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Most of the studies have not shown any negative effect of a pregnancy on long-term disease course/progression or disability [32]; some even reported favorable effects [12,29,31]. We showed that MS patients who had only 1 pregnancy had a higher conversion rate from RRMS to SPMS than MS patients with 2 or more pregnancies (p = 0.001).…”
Section: Discussionsupporting
confidence: 53%
“…Some data suggested small beneficial effect of pregnancy on long-term MS outcome [4,10,11,12,13]. However, patients with more aggressive disease might choose not to have children and that may cause selection bias in those studies.…”
Section: Introductionmentioning
confidence: 99%
“…This turned out to be untrue. Some studies suggest pregnancy conveys a long-term benefit [Keyhanian et al 2012;Masera et al 2015;Runmarker and Andersen 1995;Verdru et al 1994], while others find no long-term impact [Karp et al 2014;Ramagopalan et al 2012]. The most accurate current counseling would be to inform patients that pregnancy has no negative effect on long-term prognosis.…”
Section: Pregnancy Impact On Prognosismentioning
confidence: 99%
“…The single best predictor for postpartum relapse is the pre‐pregnancy relapse rate . MS relapses occur less often in parous women, and pregnancy after MS onset is associated with a lower risk of progression . A recent systematic review by McKay et al .…”
Section: Effect Of Pregnancy and Breastfeeding On Msmentioning
confidence: 99%